Predictive biomarkers of performance under stress: a two-phase study protocol to develop a wearable monitoring system - Flintoff, J. M.; Pattinson, C.; Ahamed, S.; Ali, S.; Bagley, A.; Broszczak, D.; Crewther, B.; de Waal, L.; Edmed, S. L.; Fernando, T.; Fookes, C.; Frentiu, F. D.; et al. (BMJ Open Sport & Exercise Medicine, 2025)
Understanding and predicting individual responses to common stressors is essential for optimising performance in high-stress environments. This article outlines a protocol for a study to identify biomarkers that predict performance under heat, musculoskeletal, psychosocial and sleep stress, for future integration into a wearable sensor system. In Phase I, healthy adults aged between 18 and 45 years (n=104) will be recruited for an intervention trial that involves exposure to one of the four stressors: heat, musculoskeletal, psychosocial or sleep deprivation. Biomarkers will be identified from molecular markers in biological samples (eg, blood, saliva, sweat and stool), physiological measures and psychological assessments to predict cognitive and physical performance under stress. A within-subjects design will determine changes in molecular and non-molecular markers before and after stress exposure. In Phase II, we will use the biomarkers identified in Phase I to develop a wearable sensor to predict and monitor human performance under stress.